Trends in mesothelioma mortality rates in South Africa: 1995–2007. Issue 7 (19th March 2011) - Kielkowski, D; Nelson, G; Bello, B; Kgalamono, S; Phillips, J I
Abstract : Objective: In 1984, South Africa had one of the highest mesothelioma rates in the world. The objective of this analysis was to calculate mesothelioma mortality rates in the South African population from 1995 to 2007. Methods: Annual mortality data and midyear population estimates were used to compute mortality rates by age group and gender for each year. The WHO World Standard Population was used as the reference population to calculate age-adjusted rates. Poisson regression models were used to test for trends. Results: In total, 2509 deaths due to mesothelioma were identified in the study period: 1920 in men and 588 in women. There were no significant trends in mesothelioma mortality rates: age-adjusted mortality rates fluctuated from 11 to 16 and from 3 to 5 per million per year for men and women, respectively. Conclusion: These mortality rates are much lower than expected, given the historical production and use of, and high exposure to, asbestos in South Africa. Possible reasons for this are discussed, including the effect of HIV which has been instrumental in reducing the life expectancy of South Africans in the last two decades. Asbestos-exposed individuals may not live long enough to develop mesothelioma. Competing causes of death need to be taken into account when constructing models to predict mesothelioma mortality rates.